Circularity Between Aquaponics and Anaerobic Digestion for Energy Generation - Juliana Lobo Paes; Cirlene Gomes Guimarães; Alexia de Sousa Gomes; Romulo Cardoso Valadão; Daiane Cecchin; Regina Menino (AgriEngineering)
Aquaponics integrates aquaculture and hydroponics, promoting circularity through the recirculation of water and nutrients. However, waste management remains a challenge. This study aimed to evaluate the anaerobic digestion (AD) of aquaponic effluent (AE) combined with cattle manure (CM) for biogas production. An Indian model biodigester was fed with AE, CM and 1:1, 1:3, and 3:1 W (Water):CM, under anaerobic mono-digestion (MoAD) and 1:1, 1:3, and 3:1 AE:CM under anaerobic co-digestion (CoAD) conditions. The chemical characteristics of the substrates and digestates were assessed, as well as the potential for biogas production over 19 weeks. Overall, CoAD provided better results regarding the chemical characterization of the substrates aimed at biogas production. Notably, the 1:3 AE:CM ratio resulted in the most promising outcomes among the tested conditions. This ratio demonstrated higher efficiency, initiating biogas production by the third week and reaching the highest accumulated volume. It is probable that AE increased the dissolved organic load, optimizing the conversion of organic matter and eliminating the need for additional water in the process. Thus, the CoAD of AE and CM emerged as a promising alternative for waste valorization in aquaponics, contributing to renewable energy generation, agricultural sustainability, and the promotion of the circular economy.